2010
DOI: 10.1097/brs.0b013e3181c5fb21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Degree of Osteoporosis on the Biomechanical Anchoring Strength of the Sacral Pedicle Screws

Abstract: For BMD value more than 0.70 g/cm, bicortical sacral pedicle screw fixation could obtain sufficient anchoring strength comparable with the PMMA augmented technique. When BMD value is within 0.6 to 0.7 g/cm, the PMMA augmented technique would be more beneficial in improving the fixation strength than the bicortical fixation. For BMD values less than 0.6 g/cm, early screw loosening may occur in both bicortical and PMMA augmented fixations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In osteoporotic patients, the abnormal bone mass can affect the mechanical properties of the bone (23) and may lead to low back pain, disc degeneration or wedge fracture of the vertebral body (45678). Moreover, the decreased bone mass of the cervical vertebrae is closely related to loosening of the spinal surgical implant screws and the artificial inter-vertebral disc substitutes (910). …”
Section: Introductionmentioning
confidence: 99%
“…In osteoporotic patients, the abnormal bone mass can affect the mechanical properties of the bone (23) and may lead to low back pain, disc degeneration or wedge fracture of the vertebral body (45678). Moreover, the decreased bone mass of the cervical vertebrae is closely related to loosening of the spinal surgical implant screws and the artificial inter-vertebral disc substitutes (910). …”
Section: Introductionmentioning
confidence: 99%
“…A variety of designs and surgical techniques have been implemented, both clinically and in laboratory settings, in an attempt to enhance the amount of fixation possible between the pedicle screw and the surrounding bone of osteoporotic patients. One method includes augmenting the screw with a bone cement, such as polymethylmethacrylate (PMMA), calcium phosphate (CaP), and hydroxyapatite (HA), which can dramatically increase the purchase of screws in the vertebral body [11, 13, 1529]. Another approach for improving the screw fixation is design alteration, which includes modifications to the diameter [3032], length [32, 33], thread design [3438], and tapering of the inner diameter of the screw [17, 30, 38, 39].…”
Section: Introductionmentioning
confidence: 99%
“…Our review of the literature found that most of the current research on pedicle screw pullout has been performed with cylindrically shaped pedicle screws [4,5,7,18-20]. Cross sections of pedicles at the lumbar spine have an elliptical shape.…”
Section: Introductionmentioning
confidence: 99%